SELECTION OF BASIC COMPETENCY FOR CANDIDATE CIVIL SERVANTS IN INDONESIA 2018: PROBLEMS AND RECOMMENDATIONS - Wisber Wiryanto (Equity: Jurnal Ekonomi, 2019)
Basic Competency Selection Candidates for Civil Servants in 2018 have the following problems: First, the passing-grade information of SKD-CPNS which was stated based on the regulation of MENPANRB No. 37/2018 but in fact not everything is based on that regulation. The reasons are: (1) SKD passing-grade score is the minimum score that must be fulfilled by each CPNS selection participant, not exceeding the passing grade score; (2) SKD-CPNS passing grade scores of athletes who excel are not stated in the SKD-CPNS passing-grade information, even though they should be determined, the lowest score of the CPNS selection participants who excel is the passing grade of SKD results; (3) Scores of the General Intelligence Test (TIU) formation of specialist doctors and pilot instructors who are required to work with very low error standards but are equated with TIU scores of general paths of at least 80. This means that the TIU scores below the cumlaude and diaspora lines are at least 85. Second, the graduation of the 2018 SKD-CPNS participants nationally is very small, only 3%. Most participants did not meet the passing grade score of 143 Personal Characteristics Test (TKP) which was too high, in contrast to the score of Nationality Insights Test (TWK) 75 and lower TIU 80. The SKD-CPNS issue requires recommendations because after a week of selection, the government agency has not yet announced the graduation of SKD-CPNS participants. Need to review SKD-CPNS passing-grade information so that it is in accordance with the regulation of MENPANRB No. 37/2018. The TKP passing grade score is too high (143), when compared with TWK scores (75) and TIU (80) which are much lower. Therefore the TKP score should be lowered and the determination of graduation based on the best ranking needs to be applied.